Adaptation to the New World: Experiences of Bereaved Families of the Patients with Coronavirus Disease 2019 - Mahmood Motamedzadeh; Marzieh Pazokian; Hanieh Molaee (Mashhad University of Medical Sciences, 2021)
Background: Acceptance of others' death is inherently difficult; therefore, throughout history, humans have avoided facing the reality of death. Mourning is a difficult experience in itself, and with Coronavirus 2019 (COVID-19), it may become more complicated.Aim: This study aimed to explain the experience of bereaved families of patients with COVID-19.Method: This qualitative descriptive study used the conventional content analysis method. In total, 20 participants were purposefully selected and included in the study. The data were obtained through in-depth semi-structured interviews. Participants' contact numbers were extracted from the archives of deceased COVID-19 patients hospitalized in the COVID-19 wards of educational hospitals of Shahid Beheshti University of Medical Sciences from August 22, 2020, to May 21, 2021, Tehran, Iran. The interviews continued until the data saturation. The interview lasted between 35 and 40 minutes. MAXQDA software (version 10) was used to analyze information.Results: The final theme of adaptation to the new world includes psychological symptoms (disbelief mourning and disease, and social stigma), role conflict (threatening context of multiple roles, bottleneck of mental and work hazards, and uncertain future), and miracle of belief and faith (inner peace with praying and distraction of thoughts).Implications for Practice: Given that one of the main concerns of the world following the COVID-19 pandemic is incomplete mourning and the resulting psychological disorders in the family, it is important to find a solution to support bereaved families to adapt to the new world without the deceased.